The influence of the external ankle support on the dynamic balance in volleyball athletes - Manuela Azevedo Correia de Lima; Germanna de Medeiros Barbosa; Joseanne Daniele Cezar Ribeiro; José Jamacy de Almeida Ferreira; Palloma Rodrigues de Andrade; Heleodório Honorato dos Santos (Universidade Estadual Paulista (UNESP), 2015)
AbstractThe purpose of this study was to assess the effect of ankle external supports on proprioception and dynamic balance in volleyball players. Seventeen female volleyball players (18.94±2.49 years; 65.45±9.49 kg; 1.71±0.05 m; BMI=22.0±2.67 kg/m²) took part in this study. The dynamic balance was assessed through the Star Excursion Balance Test (SEBT). Comparisons between stabilization (no stabilizer/NS, orthosis/ORT and functional bandaging/FB) modes and the SEBT grid lines and inter-limb were carried out. The SEBT assessment showed a significant difference between the groups NS x ORT and NS x FB (p < .01), and between the lines (p< .01). Significant line/limb interaction in DL and NDL (p< .01) was detected. The external supports tested herein showed similar effects on balance, restricting lower limb's reach in the SEBT execution in some of tested directions.